Investigation on Computerized Maintenance Management System (CMMS) for government project / Muhamad Shahriman Othman - Othman, Muhamad Shahriman (2011)
Information technology nowadays plays an important role in building maintenance management. Information is needed to analyze study and examine what is occurring and properly control the maintenance of facility in building. Computerized Maintenance Management System (CMMS) are computer program to control the maintenance organization. CMMS can improve efficiency, reduce cost, provide historical report, increase the life of building and provide maintenance report .Maintenance should be planned to determine the cause of damage. The purpose of this study is to produce a system of computerized maintenance management to improve the operating of maintenance. Manual Method in building maintenance can be optimized through the use of computerized maintenance management system. Data Mining can be turn into useful information with the process of analyzing data from different perspective. The data collect through interview and questionnaire with the person in maintenance management and make some recommendation to improve the use of data mining from CMMS.